PENGARUH PENGGUNAAN BUSANA DAN AKSESORIS KARYA VIVIENNE WESTWOOD DALAM MANGA DAN ANIME NANA TERHADAP TREND FASHION HARAJUKU PUNK-ROCK DI JEPANG - Zulaikha Yaffa (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
This paper discusses the fashion trend introduced in the Japanese anime series entitled Nana, and its influence on the fashion industry in Japan. The series features Nana’s story while portraying the fashion trend among the main characters that is best described as the combination of Harajuku style. The objective of this paper is to explain how Nana anime series influenced fashion trend especially punk-rock subculture among Japanese youngsters. The research employs qualitative research method and Dominic Strinati’s theory on popular culture. It shows that the fashion trends among Japanese youths were influenced by the fashion style shown in the anime series. It appears that the usage of manga and anime as channels for marketing strategy has become more effective to reach and influence wide audience faster, compared to expensive commercials with celebrity stars. This is especially true because anime and/or manga have fanatic audience with the tendency to imitate their favourite characters.